Keberlanjutan Pengelolaan Lingkungan Pesisir Melalui Pemberdayaan Masyarakat di Desa Kwala Lama Kabupaten Serdang Bedagai - Fitriansah, Herry (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
Fisherman community of Kwala Lama District in Serdang Bedagai Regency, North Sumatera has conducted a community based environmental management program known as the PLBM (pengelolaan Lingkungan Berbasis Pemberdayaan Masyarakat), to help restore the coastal environmental damage in the area. The study aims to identify the processes and changes that are taking place within the sustainable environmental management activity. The study employs (1) environmental, social and economic change analysis, (2) community behavior and attitude analysis, and (3) sustainable community construction process analysis. The study concludes that the community participation approach in environmental management implemented in the PLBM program has in fact encouraged many changes which lead to the community’s improvement of social and economic conditions. The study found that the facilitator group selection process conducted by the administration at the preliminary stage has indeed been successfully carried out, enabling the group to carry out the program fairly and accountably, hence developing trust from the community. The program has also developed solidarity thus rendering the community ready to be fully responsible of environmental management and to continue the program.